2019
DOI: 10.1177/1925362119891705
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autophagy Biomarkers In Burn-Age Estimation and Progression

Abstract: Background: Determination of time passed since burn injury in the living is critical in forensic science. Autophagy biomarkers and vitronectin can play an important role in determination of the age of burn injuries through their levels in the tissue. Objective: The aim of this study was to investigate the role of autophagy biomarkers in dating burn injury and to correlate them with the histopathological effects of deep second-degree thermal burn. Method: Fifty-four male rats were used in this study after infli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Thermal injuries are a common and severe acute traumatic event. In forensic science, determining the timing of a burn injury in a living person is critical [17]. In our study, accidental burns were the most predominant and no homicidal cases were reported.…”
Section: Discussionmentioning
confidence: 62%
“…Thermal injuries are a common and severe acute traumatic event. In forensic science, determining the timing of a burn injury in a living person is critical [17]. In our study, accidental burns were the most predominant and no homicidal cases were reported.…”
Section: Discussionmentioning
confidence: 62%